Echocardiographic integrated backscatter for the differentiation between aortic valve calcification and valvular myxoid degeneration in rats. (1st September 2014) - Gillis, Kris; Bala, Gezim; Roosens, Bram; Remory, Isabel; De Raeve, Hendrik; Tierens, Simon; Hernot, Sophie; Van Camp, Guy; Droogmans, Steven; Cosyns, Bernard
Abstract: Aims: Calcification is an independent predictor of mortality in aortic valve (AV) stenosis. Echocardiographic calibrated integrated backscatter (cIB) is a promising parameter for quantifying AV calcification. However, the ability of cIB to differentiate between calcification and valvular thickening has been questioned. Therefore, we aimed to use cIB to study AV calcification compared with non-calcified AV thickening in rats, with histology as reference. Methods and results: Twenty male Wistar rats were studied. Group 1 ( N = 6) received subcutaneous (SC) serotonin injections (60 mg/kg/day) for 12 weeks to induce myxoid non-calcified AV thickening. Group 2 ( N = 7) received vitamin D3 (25 000 UI/kg/day) SC to induce AV calcification, and Group 3 ( N = 7) received only vehicle SC for 10 weeks. cIB of the AV was calculated at the end of the study, followed by measurement of the percentage of the histological AV calcification. At the end of the study, cIB values and calcification percentages were significantly higher in vitamin D3 -injected rats compared with serotonin-injected rats and controls. There was no significant difference in cIB values between serotonin-injected rats and controls (vitamin D3 : 21.5 ± 3.0 dB*; serotonin: 11.8 ± 3.1 dB; control: 10.3 ± 3.4 dB; * P < 0.05). The percentage of histological calcification was significantly higher in the vitamin D3 group compared with the other groups. Serotonin-injected rats developed significant AV thickening. Conclusion: Increased cIB values of the AV are related to increased calcification at histology and not to myxoid non-calcified valvular thickening. Therefore, cIB may be considered as a sensitive technique to quantify calcification of AV rather than for detecting non-calcified valvular thickening.